Trends in innovative pediatric drug development in China based on clinical trial registration data - Wu, Wen-Wen; Ji, Xing; Mou, Xin-Shuang; Ma, Xin-Yue; Huang, Ya-Ting; Zhang, Jie-Ying; Zhang, Jing-Xian; Xie, Xin-Rong; Mao, Ning-Ying; Xu, Jing (Frontiers in Medicine, 2023)
In China, the focus of drug research and development has gradually shifted from generic to innovative drugs. Using the Chinese Clinical Trials Registry and Information Transparency Platform, we retrospectively analyzed clinical trials of innovative pediatric drugs conducted in mainland China over the last decade. The goal of this work was to better understand the characteristics of and historical changes in innovative pediatric drug research and development (R&D) in China and to provide effective data support for policy makers and other stakeholders. This study included 198 innovative pediatric drug clinical trials. The data showed that, although some progress has been made in the R&D of innovative pediatric drugs in China, many factors limiting this progress still exist, such as concentrated R&D areas, inadequate pediatric participants, and unbalanced source distributions. The level of innovative pediatric drug R&D in China currently lags behind the global level and has not kept pace with anti-neoplastic drug R&D in China. To promote the innovative development of pediatric drugs in China, the Chinese government must develop an R&D supervision framework, improve the motivation and innovation capabilities of pharmaceutical companies, and optimize the source distribution between regions.